1999
DOI: 10.1192/bjp.174.4.339
|View full text |Cite
|
Sign up to set email alerts
|

Depression symptoms in late life assessed using the EURO–D scale

Abstract: Large between-centre differences in depression symptoms were not explained by demography or by the depression measure used in the survey. Consistent, small effects of age, gender and marital status were observed across Europe. Depression may be overdiagnosed in older persons because of an increase in lack of motivation that may be affectively neutral, and is possibly related to cognitive decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
91
1
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(110 citation statements)
references
References 32 publications
11
91
1
7
Order By: Relevance
“…The report of any limitations in the activities of daily living (ADL) 4 and in the instrumental activities of daily living (IADL) 5 can be viewed as more objective, as the individual has no reason to relate this rather factual information directly to her health. As a measure for clinical depression, the EURO-D scale (see Prince et al, 1999a) has been implemented in SHARE, where, as was validated in Prince et al (1999b), an indicator for a score of at least four on the scale is taken as a measure for clinical depression. The final objective measure is orientation in time,…”
Section: Model and Variablesmentioning
confidence: 99%
“…The report of any limitations in the activities of daily living (ADL) 4 and in the instrumental activities of daily living (IADL) 5 can be viewed as more objective, as the individual has no reason to relate this rather factual information directly to her health. As a measure for clinical depression, the EURO-D scale (see Prince et al, 1999a) has been implemented in SHARE, where, as was validated in Prince et al (1999b), an indicator for a score of at least four on the scale is taken as a measure for clinical depression. The final objective measure is orientation in time,…”
Section: Model and Variablesmentioning
confidence: 99%
“…In general, poorer mental health is typically found among women (Lehtinen et al 2005;Carta et al 2005;Prince et al 1999b;Alonso et al 2004). Copeland et al (1999b) assessed the prevalence of depression among individuals aged 65+ in nine European centres and found that also in this respect women outnumber men in the group of older people.…”
Section: Other Determinants Of Mental Healthmentioning
confidence: 99%
“…Many studies also show an increase in depressive symptoms with age (Newman and Engel 1991; Prince et al 1999b;Schoevers et al 2000). This association, however, is not always clear (Weissman et al 1988).…”
Section: Introductionmentioning
confidence: 99%
“…It has been consistently found that women suffer more from depression than men (Pahkala et al 1995;Prince et al 1999b;Osborn et al 2002). Many studies also show an increase in depressive symptoms with age (Newman and Engel 1991; Prince et al 1999b;Schoevers et al 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation